2009
DOI: 10.1590/s0103-64402009000200005
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of endodontic irrigants containing calcium hydroxide and sodium lauryl sulphate on fibroblasts derived from mouse L929 cell line

Abstract: The aim of this study was to evaluate the cytotoxicity of root canal irrigating solutions containing calcium hydroxide and sodium lauryl sulphate on fibroblasts derived from L929 cell line. Saturated calcium hydroxide aqueous solution (CH), sodium lauryl sulphate (SLS) and SLS associated with calcium hydroxide (HCT20) were diluted with sterile distilled water at 50%, 20%, 10% and 5% concentrations. Minimum essential medium (MEM) served as the control group. The cytotoxicity of the solutions was evaluated on L9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Calcium hydroxide is the gold-standard material for the treatment of root canals, which feature antimicrobial activity, mechanical blockage to avoid canal reinfection, limitation of root resorption, induction of mineralized tissue, and promotion of periapical and adjacent tissue repair [9,19] with secondary anti-inflammatory action. This intracanal medication presented no genotoxicity but showed cytotoxicity, also observed in other studies [20,21]; however, some authors disagree with these findings [22,23]. This inconsonance may be related to the…”
Section: Discussionsupporting
confidence: 51%
“…Calcium hydroxide is the gold-standard material for the treatment of root canals, which feature antimicrobial activity, mechanical blockage to avoid canal reinfection, limitation of root resorption, induction of mineralized tissue, and promotion of periapical and adjacent tissue repair [9,19] with secondary anti-inflammatory action. This intracanal medication presented no genotoxicity but showed cytotoxicity, also observed in other studies [20,21]; however, some authors disagree with these findings [22,23]. This inconsonance may be related to the…”
Section: Discussionsupporting
confidence: 51%
“…[ 35 ] Barbosa stated the association of calcium hydroxide and sodium lauryl sulfate combines the beneficial properties of these solutions and was not harmful to the fibroblast cell line, seeming to be a suitable endodontic irrigating solution. [ 36 ]…”
Section: Discussionmentioning
confidence: 99%
“…reported that a combination of calcium hydroxide and SDS can be used as an endodontic irrigant. [ 33 ] Fiume et al . reported that SDS in products intended for prolonged contact with the skin, concentrations should not exceed 1%.…”
Section: Discussionmentioning
confidence: 99%